Application of ARIMA Modelling for the Forecasting of Solar, Wind, Spot and Options Electricity Prices: The Australian National Electricity Market - Alsaedi, Yasir; Tularam, Gurudeo Anand; Wong, Victor (International Journal of Energy Economics and Policy, 2019)
This study aims to develop autoregressive integrated moving average (ARIMA) models to predict the solar, wind, spot and options pricing over the next two years, with historical data being used in a univariate manner to understand market behaviour in terms of trends. The assessment is made in the context of the Australian National Electricity Market (ANEM). The ARIMA models predict the future values of the monthly solar, wind, spot and options prices for various Australian states using time-series data from January 2006 to March 2018. The results show increases from 30.46–40.42% for the spot electricity prices and from 14.80–15.13% for the options electricity prices in the ANEM with a two-year horizon. The results further show that wind prices are expected to increase by an average of 5.43%. However, the results also show that the average solar electricity prices will decrease by 67.7%. Keywords: Electricity pricing, ARIMA model, Forecasting. JEL Classifications: C22, E37, Q47 DOI: https://doi.org/10.32479/ijeep.7785